2014
DOI: 10.1080/01635581.2014.936948
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Anticancer Activity of Curcumin Using Nanocurcumin Dispersion in Water

Abstract: Curcumin is a highly potent, nontoxic bioactive agent found in turmeric and is known to have significant anticancer properties against different types of cancer cells. The major disadvantage associated with the use of curcumin, however, is its low systemic bioavailability due to its poor aqueous solubility. The focus of the present study was to generate nanoparticles of curcumin with improved aqueous phase solubility, and to investigate their efficacy in treating cancer cells. Curcumin nanoparticles having par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…In a polar medium, curcumin has the unique ability to perforate into the cell and with an excellent electron transfer capability can facilely enter into the plasma membrane of the cell. Hence, the particle size of curcumin nanoparticles demonstrated better aqueous phase solubility and having much more vigorous anticancer effect against various cancer cell lines [ 148 ]. Consequently, nano formulations of curcumin showed ameliorated therapeutic efficacy compared to bulk or native curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…In a polar medium, curcumin has the unique ability to perforate into the cell and with an excellent electron transfer capability can facilely enter into the plasma membrane of the cell. Hence, the particle size of curcumin nanoparticles demonstrated better aqueous phase solubility and having much more vigorous anticancer effect against various cancer cell lines [ 148 ]. Consequently, nano formulations of curcumin showed ameliorated therapeutic efficacy compared to bulk or native curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocurcumin was found to be more effective in its antiproliferative properties compared to native curcumin in MDA breast cancer cell lines [10]. Likewise, compared to native curcumin, curcumin nanoparticles exhibited stronger inhibitory properties against cell proliferation in lung A549, liver HepG2 and skin A431 cells [11]. PLGA nanoparticles encapsulating curcumin and amyloid-beta generating inhibitor attenuated memory deficit and neuropathology in a mice model [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the work of Basniwal et al [22] showed reducing the particle size of curcumin in the nanometer range not only improves its aqueous phase solubility and cellular uptake but also enhances its activity as an anticancer agent. The results also showed that curcumin nanoparticles have better antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%